2001
DOI: 10.1155/2001/304098
|View full text |Cite
|
Sign up to set email alerts
|

N‐CDAD in Canada: Results of the Canadian Nosocomial Infection Surveillance Program 1997 N‐CDAD Prevalence Surveillance Project

Abstract: BACKGROUND:A 1996 preproject survey among Canadian Hospital Epidemiology Committee (CHEC) sites revealed variations in the prevention, detection, management and surveillance ofClostridium difficile-associated diarrhea (CDAD). Facilities wanted to establish national rates of nosocomially acquired CDAD (N-CDAD) to understand the impact of control or prevention measures, and the burden of N-CDAD on health care resources. The CHEC, in collaboration with the Laboratory Centre for Disease Control (Health Canada) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The rates are remarkably similar to those found in our previous study [7]; however, we found wide variations in HA CDI among the participating hospitals (range, 20-167 cases per 100,000 patients-days). The underlying reasons for this variation remain unclear.…”
Section: Discussionsupporting
confidence: 90%
“…The rates are remarkably similar to those found in our previous study [7]; however, we found wide variations in HA CDI among the participating hospitals (range, 20-167 cases per 100,000 patients-days). The underlying reasons for this variation remain unclear.…”
Section: Discussionsupporting
confidence: 90%
“…C. difficile vegetative cells produce toxins A and B and hydrolytic enzymes (1). Local production of toxins A and B leads to production of tumour necrosis factor-alpha and proinflammatory interleukins, increased vascular permeability, neutrophil and monocyte recruitment (2), opening of epithelial cell junctions (3) and epithelial cell apoptosis (4). Local production of hydrolytic enzymes leads to connective tissue degradation, leading to colitis, pseudomembrane formation (5) and watery diarrhea.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…3 There is an overall impression that there has been an increase in the proportion of CDAD cases with severe and fatal complications and an increase in the relapse rate among affected patients. A 1997 Canadian survey 4 indicated that the attributable case-fatality rate to be 1.5%, and other authors have reported an attributable mortality of 0.8 to 2% for nosocomial CDAD.…”
mentioning
confidence: 99%
“…1,2 Studies in the United States and Canada have shown that public-and private-sector policies limiting drug coverage lead to fewer prescriptions being filled, 3,4 higher rates of nursing home admissions 5 and increased use of acute care services. 3 Yet physicians often fail to identify patients who are burdened by high out-of-pocket expenses. 6 Many patients with chronic illnesses who report having underused medications because of cost never discuss this underuse with their physicians.…”
mentioning
confidence: 99%